Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
Keywords: dept.eco; dept.fin; peer-reviewed

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found